2014
DOI: 10.1111/eth.12334
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Reciprocal Allonursing in Reindeer, Rangifer tarandus

Abstract: The nursing of non‐offspring is referred to as allonursing. Reciprocity is a hypothesized cause of allonursing, but previous studies have not strongly supported or found no evidence in support for this hypothesis. Biological market theory was applied to 25 reindeer (Rangifer tarandus) does and their calves to investigate allonursing reciprocity across bouts and within dyads and assess the diversity of allonursing partners. We also investigated whether variation in allonursing would be associated to relatedness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 74 publications
(233 reference statements)
0
20
0
Order By: Relevance
“…Some non-mutually exclusive hypotheses have been proposed to explain why lactating females nurse alien offspring: misdirected parental care (Packer et al, 1992), reciprocity (Ekvall, 1998;Engelhardt et al, 2015;Glonekov et al, 2016), kin selection (Pusey and Packer, 1994;Ekvall, 1998;Eberle and Kappeler, 2006;Engelhardt et al, 2016), evacuation of leftover milk (Riedman and Le Boeuf, 1982;Wilkinson, 1992), inexperience of females (Murphey et al, 1991;1995), and milk theft (Murphey et al, 1995;Maniscalco et al, 2007;Zapata et al,2009;Engelhardt et al, 2014;Glonekov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Some non-mutually exclusive hypotheses have been proposed to explain why lactating females nurse alien offspring: misdirected parental care (Packer et al, 1992), reciprocity (Ekvall, 1998;Engelhardt et al, 2015;Glonekov et al, 2016), kin selection (Pusey and Packer, 1994;Ekvall, 1998;Eberle and Kappeler, 2006;Engelhardt et al, 2016), evacuation of leftover milk (Riedman and Le Boeuf, 1982;Wilkinson, 1992), inexperience of females (Murphey et al, 1991;1995), and milk theft (Murphey et al, 1995;Maniscalco et al, 2007;Zapata et al,2009;Engelhardt et al, 2014;Glonekov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals must remember with whom they interacted before, and how a particular social partner behaved towards them in previous interactions 3 . Evidence for direct reciprocity among animals exists both from observations in nature and from experimental studies 6 7 8 9 10 11 12 13 , reviewed in refs 14 , 15 , 16 , 17 , 18 . In contrast to direct reciprocity, generalised reciprocity implies that individuals help others if they received help from someone else.…”
mentioning
confidence: 99%
“…In this study, it was found that giraffe allonursed non-filial calves reciprocally, further supporting the reciprocity hypothesis as the primary explanation for allonursing amongst captive giraffe. While this hypothesis did not receive much support in the past 13 , recent studies involving ungulates provided evidence in support of reciprocity, explained by allosuckling ( Equus grevyi 32 ; Rangifer tarandus 28 ; Giraffa camelopardalis 19 , Bison bison 29 ). The current study revealed that allosuckling frequencies and time devoted to allosuckling increased concomitantly in dyad A and dyad B, corresponding with the reciprocity hypothesis which assumes that two females achieve higher fitness when nursing each other's offspring.…”
Section: Discussionmentioning
confidence: 96%